Open‐circuit fault diagnosis method for three‐level neutral point clamped inverter based on instantaneous frequency of phase current - Shuiqing Xu; Juxing Wang; Mingyao Ma (Energy Conversion and Economics, 2020)
Abstract Because the three‐level neutral point clamped (NPC) inverter has the advantages of a large output capacity and high output voltage, it is widely used in wind energy and solar energy power generation. Unfortunately, the three‐level NPC inverter often suffers from open‐circuit faults, which leads to system security problems and great economic losses. To guarantee the secure operation of the three‐level NPC inverter, an open‐circuit fault diagnosis method for a three‐level NPC inverter based on the instantaneous frequency (IF) of the phase current is proposed here. First, different open‐circuit fault signals of the NPC inverter are analysed. Then, the IF of the phase current is used to obtain the fault diagnosis variables. Simultaneously, the Hilbert transform (HT) is used to estimate the IF of the phase current, which carries the information of open‐circuit faults. Meanwhile, the average value of the normalised current is provided to locate faulty switches. Finally, by combining the diagnostic variables with the identification threshold, the detection and localisation of open‐circuit faults in the NPC three‐level inverter are determined. Compared to other fault diagnosis methods, the proposed method is more stable and makes it easier to diagnose open‐circuit faults. The correctness and robustness of the method are verified by simulation results.